Carbon-assisted synthesized FeCoNiCuMo / C-coated NF multi-metal composite material as well as preparation method and application thereof

Through carbon-assisted synthesis of FeCoNiCuMo/C@NF polymetal composites, the existing electrolytic hydrogen production catalysts have been solved, and low-cost and high-catalytic activity catalysts have been achieved, which are suitable for HER, OER and full water-removing catalysis of electrolytic hydrogen production.

CN119615251APending Publication Date: 2025-03-14CHAOHU UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411779769.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing electrolytic hydrogen production catalyst has high cost and short service life, making it difficult to achieve economical and sustainable development.

Method used

Through carbon-assisted synthesis of FeCoNiCuMo/C@NF polymetal composite materials, leverage the advantages of polymer support and porous metal support to couple transition metal elements in situ to synthesize one-dimensional FeCoNiCuMo/C@NF composite catalysts on the surface of foam nickel to improve metal dispersion and catalytic activity.

Benefits of technology

It achieves low-cost, high-catalytic activity catalysts, surpassing the performance of precious metal catalysts, and is suitable for HER, OER and full water-removing catalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615251A_ABST
    Figure CN119615251A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-assisted synthesized FeCoNiCuMo / C-coated NF multi-metal composite material and a preparation method and application thereof.The preparation method comprises the steps that a nitrogen-containing polymer is dispersed in water to serve as a solution A; a molybdenum source, urea, NH4F, a nickel source, a cobalt source, an iron source and a copper source are mixed and dispersed in a solvent to serve as a solution B; dropwise adding the solution B into the solution A, stirring, adding foamed nickel into the obtained mixed solution, and carrying out hydrothermal reaction to obtain a precursor; and carrying out pyrolysis in a hydrogen and argon mixed atmosphere to obtain the FeCoNiCuMo / C-coated NF multi-metal composite material. Compared with the prior art, the preparation method has the advantages that through a simple synthesis mode of one-step hydrothermal and one-step pyrolysis, the advantages of the polymer derived carbon carrier and the porous metal carrier are coupled, and the structural stability of the catalyst is improved; the one-dimensional nanorod structure has unique structural advantages, so that more active sites can be exposed, and the catalyst has HER and OER performance superior to those of noble metal and complete water splitting performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology and material preparation, and specifically relates to a carbon-assisted synthesis FeCoNiCuMo / C@NF multi-metal composite material and a preparation method and application thereof, and application in electrocatalytic water decomposition. Background Art

[0002] Under the dual challenges of energy structure transformation and environmental protection, water electrolysis hydrogen production technology is becoming increasingly important as a clean and sustainable way to produce hydrogen energy. However, the catalytic efficiency of water electrolysis hydrogen production is still the core bottleneck of its commercial application, mainly due to the cost and efficiency of the catalyst.

[0003] At present, precious metal catalysts such as platinum and iridium are widely used in business. Although they have excellent catalytic performance, their cost has increased significantly due to the scarcity of precious metal resources, which directly affects the economic feasibility of hydrogen production by electrolysis of water. In addition, precious metal catalysts are susceptible to poisoning and wear, resulting in reduced catalytic activity and service life. Over-reliance on these resources may also aggravate environmental degradation and resource depletion. Therefore, researchers are actively exploring new catalysts in order to effectively reduce costs while ensuring catalytic efficiency and achieve sustainable development.

[0004] The incompletely filled d-band electronic structure of transition metals provides the possibility for the controlled synthesis of high-performance non-precious metal catalysts. In particular, the combination of different transition metal elements has been developed as an efficient electrocatalyst. However, issues such as coupling, proportion, and sintering agglomeration between metals need to be further studied and resolved.

[0005] In this context, it is necessary to develop high-performance and low-cost catalysts. Summary of the invention

[0006] The purpose of the present invention is to provide a carbon-assisted synthesis of FeCoNiCuMo / C@NF multi-metal composite material and a preparation method thereof, which utilizes the advantages of polymer carriers and porous metal carriers, and in-situ couples cheap transition metal elements such as Ni, Mo, Co, Fe, and Cu to synthesize a one-dimensional FeCoNiCuMo / C@NF composite catalyst on the surface of nickel foam (NF), thereby improving the metal dispersion, utilizing the electronic regulation and microstructure design between multiple elements, improving the catalytic activity of the catalyst, and reducing the cost, thereby improving the current situation that the electrolytic water catalyst is expensive and has a limited service life.

[0007] Another object of the present invention is to provide an application of a carbon-assisted synthesis of FeCoNiCuMo / C@NF multi-metal composite material for HER, OER and overall water splitting catalysis.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material comprises the following steps:

[0010] 1) Dispersing a nitrogen-containing polymer in water as solution A; mixing and dispersing a molybdenum source, urea, NH4F, a nickel source, a cobalt source, an iron source and a copper source in a solvent as solution B; dropping solution B into solution A, stirring, adding nickel foam to the obtained mixed solution, performing a hydrothermal reaction, and obtaining a precursor;

[0011] 2) The precursor is pyrolyzed in a mixed atmosphere of hydrogen and argon to obtain a FeCoNiCuMo / C@NF multi-metal composite material.

[0012] The mass ratio of the nitrogen-containing polymer, the molybdenum source, the urea and the NH4F in step 1) is: 0.04-0.16: 0.1-0.4: 0.1: 0.1.

[0013] In step 1), the atomic molar ratio of Mo in the molybdenum source, Ni in the nickel source, Co in the cobalt source, Fe in the iron source and Cu in the copper source is 1:1:0.5:0.1:0.1 to 1:2:2:1:1;

[0014] The concentration of the nitrogen-containing polymer in solution A in step 1) is 1 mg / mL-6 mg / mL;

[0015] The nitrogen-containing polymer in step 1) is any one of polydopamine PDA, chitosan CS or polyethyleneimine PEI;

[0016] In step 1), the concentration of the molybdenum source in the solution B is 2.5 mg / mL-12 mg / mL;

[0017] In step 1), the solvent is a mixed solvent of anhydrous ethanol and water, and the volume ratio of anhydrous ethanol to water is 1:1;

[0018] In step 1), solution B is added dropwise into solution A.

[0019] The molybdenum source in step 1) is Keggin type phosphomolybdic acid H3PMo 12 O 40 xH2O, abbreviated as PMo 12 , sodium molybdate (Na2MoO4), ammonium molybdate ((NH4)2MoO4);

[0020] In step 1), the nickel source is selected from a soluble nickel salt, preferably a chloride, a nitrate or a sulfate, more preferably Ni(NO3)2 or NiCl2·6H2O;

[0021] In step 1), the cobalt source is selected from a soluble cobalt salt, preferably a chloride, a nitrate or a sulfate, more preferably Co(NO3)2·6H2O;

[0022] In step 1), the iron source is selected from soluble iron salts, preferably chlorides, nitrates or sulfates, more preferably FeCl3·6H2O or Fe(NO3)3·9H2O;

[0023] In step 1), the copper source is selected from soluble copper salts, preferably chlorides, nitrates or sulfates, more preferably Cu(NO3)2·6H2O;

[0024] The nickel foam in step 1) is pre-treated before use, and the specific method is: 2×5cm 2 The nickel foam (NF) was washed with ethanol and deionized water in turn, ultrasonically treated in 2M hydrochloric acid for 10-15 min, taken out, washed with deionized water and placed in a vacuum oven at 60°C for later use;

[0025] The hydrothermal reaction conditions in step 1) are: hydrothermal reaction at 150-180° C. for 6-12 hours;

[0026] In step 2), the volume percentage of hydrogen in the hydrogen and argon mixed atmosphere is 5%;

[0027] The pyrolysis in step 2) refers to heating to 400-600°C at a rate of 5°C / min and keeping the temperature for 2h;

[0028] The water described in the present invention is preferably deionized water.

[0029] Preferably, the preparation method of the present invention is:

[0030] S1. Pretreatment of nickel foam: 2×5cm 2 The nickel foam (NF) was washed with ethanol and deionized water in turn, ultrasonically treated in 2M hydrochloric acid for 10-15 min, taken out, washed with deionized water and placed in a vacuum oven at 60°C for later use;

[0031] S2. Weigh 0.04-0.16 g of nitrogen-containing polymer, add 30 ml of deionized water, and stir on a magnetic stirrer to form a uniform transparent solution A;

[0032] S3, weigh 0.1-0.4g of molybdenum source, 0.1g of urea, 0.1g of NH4F, 0.1-0.4g of nickel salt, 0.1-0.4g of cobalt salt, 0.05-0.2g of iron salt, and 0.1-0.4g of copper salt in sequence, add 40mL of a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1, and sonicate until the raw materials are completely dissolved, marked as solution B;

[0033] S4, under stirring, add solution B formed in step S3 dropwise into solution A, and stir for 15 minutes to form solution C;

[0034] S5, placing the nickel foam treated in step S1 obliquely in a polytetrafluoroethylene reactor, adding solution C, hydrothermally reacting at 150-180° C. for 6-12 h, rinsing with deionized water and drying in an oven at 60° C. to obtain a catalyst precursor;

[0035] S6. The precursor obtained in step S5 is heated to 400-600°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere, kept warm for 2 hours, and then naturally cooled to obtain a nickel foam-supported nanorod composite catalyst composed of Fe, Co, Ni, Cu, and Mo elements, named FeCoNiCuMo / C@NF.

[0036] In the preparation method of the present invention, by coupling transition metal ions with polymer molecular monomers, a multi-metal FeCoNiCuMo / C nanorod composite material is in situ grown on a 3D nickel foam (NF) porous metal substrate by a one-step hydrothermal and one-step pyrolysis method, and used as an effective bifunctional electrocatalyst for complete water splitting. The ratio regulation and dispersed distribution between multiple elements produce a strong synergistic effect between the elements, thereby improving the intrinsic activity of the catalyst. The catalyst can simultaneously exhibit HER and OER performance that surpasses precious metals and complete water splitting performance.

[0037] The present invention provides a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material, which is prepared by the above method. A large number of fine nanoparticles are distributed on the surface of the nanorods of the FeCoNiCuMo / C@NF multi-metal composite material.

[0038] The invention provides an application of a carbon-assisted synthesis FeCoNiCuMo / C@NF multi-metal composite material for HER, OER and overall water splitting catalysis.

[0039] The design ideas of the present invention are as follows: the polymer-derived carbon structure has the characteristics of stable structure and rich active sites. The polymer precursor contains rich active groups, which can achieve highly dispersed bonding to the reaction species, and then synthesize a catalyst with highly dispersed active sites to provide higher catalytic activity; at the same time, the self-supporting porous metal carrier is often used as a catalyst carrier for electrolysis of water due to its excellent conductivity, large specific surface area and good structural stability, especially its metal carrier nature has good advantages for synthesizing alloy catalysts; the present invention combines the advantages of polymer precursors and metal carriers, and adopts a synthesis method of highly dispersed in-situ coupling of multiple transition metals to solve the problems of coupling, agglomeration and sintering between multiple transition metals, and develop high-performance and inexpensive catalysts. In the technical solution of the present invention, transition metal ions are adsorbed and dispersed by polymer molecular precursors, and then a multi-metal one-dimensional nanorod complex is synthesized on a 3D porous metal skeleton by a one-step hydrothermal method. After a high-temperature pyrolysis process, the highly dispersed metal elements are alloyed. By controlling the ratio composition between the elements, the catalytic activity of the catalyst in electrolyzing water can be effectively improved, so that the catalyst can exhibit dual activity of hydrogen evolution and oxygen evolution at the same time. This work proposes a new perspective strategy, that is, to manufacture ingenious bifunctional electrocatalysts with carefully designed structures and excellent performance for use in clean energy conversion technology or storage devices.

[0040] Compared with the prior art, the present invention can effectively regulate the ratio and dispersion state of each metal by using polymer precursors to disperse transition metal precursors, thereby improving the catalytic activity of the catalyst; through a simple synthesis method of one-step hydrothermal and one-step pyrolysis, the advantages of polymer-derived carbon carriers and porous metal carriers are coupled to improve the structural stability of the catalyst; the catalyst is a one-dimensional nanorod structure, and the unique structural advantage can expose more active sites and improve the catalytic activity of the catalyst. The catalyst can simultaneously exhibit HER and OER and full water splitting performance that surpasses precious metals. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The XRD diagram of the final catalyst FeCoNiCuMo / C@NF prepared at different calcination temperatures during the implementation of Example 1 of the present invention;

[0042] Figure 2 This is the SEM spectrum of the catalyst FeCoNiCuMo / C@NF obtained in Example 1;

[0043] Figure 3 TEM spectrum of the catalyst FeCoNiCuMo / C@NF obtained in Example 1;

[0044] Figure 4 Hydrogen evolution of the catalyst FeCoNiCuMo / C@NF and the noble metal catalyst obtained in Example 1 ( Figure 3a) and oxygen evolution ( Figure 3 LSV curve of (b);

[0045] Figure 5 The full water splitting performance curves of the catalyst FeCoNiCuMo / C@NF and the noble metal catalyst obtained in Example 1. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0048] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0049] Example 1

[0050] A method for preparing a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material comprises the following steps:

[0051] 1) Size: 2×5cm 2 The rectangular nickel foam was treated with ethanol, deionized water and 2M hydrochloric acid for 15 min in sequence, rinsed with deionized water and dried in a 60°C vacuum oven for later use;

[0052] 2) Weigh 0.08 g of dopamine hydrochloride into a 50 ml beaker, add 30 ml of deionized water, and stir on a magnetic stirrer to form a uniform transparent solution A;

[0053] 3) Weigh 0.46g PMo 12 , 0.1g urea, 0.1g NH4F, 0.72g NiCl2·6H2O, 0.44g Co(NO3)2·6H2O, 0.08g FeCl3·6H2O, 0.1g Cu(NO3)2·6H2O were placed in a 50ml beaker, 40mL of a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1 was added, and ultrasonication was performed until the raw materials were completely dissolved, which was marked as solution B;

[0054] 4) under stirring, slowly add solution B formed in step 3) dropwise into solution A, stirring for 15 min to form solution C;

[0055] 5) placing the nickel foam treated in step 1) obliquely in a polytetrafluoroethylene reactor, adding solution C, hydrothermally reacting at 180° C. for 8 h, rinsing with deionized water, and drying in an oven at 60° C. to obtain a catalyst precursor;

[0056] 6) The precursor obtained in step 5) is heated to 500° C. at a rate of 5° C. / min in a hydrogen / argon mixed atmosphere with a hydrogen volume ratio of 5%, kept warm for 2 hours, and then naturally cooled to obtain a nickel foam-supported nanorod composite catalyst composed of Fe, Co, Ni, Cu, and Mo elements, named FeCoNiCuMo / C@NF.

[0057] The process was carried out according to Example 1, except that the pyrolysis temperature in step 6) was replaced with 400°C and 600°C. Figure 1 This is the XRD diagram of the final catalyst FeCoNiCuMo / C@NF prepared at different pyrolysis and calcination temperatures during the implementation of Example 1 of the present invention. In the diagram, it can be seen that alloying occurs between different transition metals inside the catalyst to form a variety of metal alloy compounds.

[0058] Figure 2 This is the SEM spectrum of the catalyst FeCoNiCuMo / C@NF obtained in Example 1. Figure 2 Figures a and b clearly show the nanorod structure grown on the surface of nickel foam. Figure 2 In the partial enlarged images of c and d, we can see that a large number of tiny nanoparticles are distributed on the surface of the nanorods.

[0059] Figure 3 TEM spectrum of the catalyst FeCoNiCuMo / C@NF obtained in Example 1. Figure 3 In a and b, we can see that the lattice structure on the nanorods is good, indicating that the metals are well bonded and there is no agglomeration.

[0060] Example 2

[0061] A method for preparing a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material comprises the following steps:

[0062] 1) Size: 2×5cm 2 The rectangular nickel foam was treated with ethanol, deionized water and 2M hydrochloric acid for 15 min in sequence, rinsed with deionized water and dried in a 60°C vacuum oven for later use;

[0063] 2) Weigh 0.08 g of dopamine hydrochloride into a 50 ml beaker, add 30 ml of deionized water, and stir on a magnetic stirrer to form a uniform transparent solution A;

[0064] 3) Weigh 0.31g PMo 12 , 0.1g urea, 0.1g NH4F, 0.95g NiCl2·6H2O, 1.2g Co(NO3)2·6H2O, 0.27g FeCl3·6H2O, 0.6g Cu(NO3)2·6H2O in a 50ml beaker, add 40mL of a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1, and sonicate until the raw materials are completely dissolved, marked as solution B;

[0065] 4) under stirring, adding solution B formed in step 3) dropwise into solution A, stirring for 15 min, to form solution C;

[0066] 5) placing the nickel foam treated in step 1) obliquely in a polytetrafluoroethylene reactor, adding solution C, hydrothermally reacting at 180° C. for 8 h, rinsing with deionized water, and drying in an oven at 60° C. to obtain a catalyst precursor;

[0067] 6) The precursor obtained in step 5) is heated to 500° C. at a rate of 5° C. / min in a 5% hydrogen / argon mixed atmosphere, kept warm for 2 hours, and then naturally cooled to obtain a nickel foam-supported nanorod composite catalyst composed of Fe, Co, Ni, Cu, and Mo elements, named FeCoNiCuMo / C@NF.

[0068] Example 3

[0069] A method for preparing a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material comprises the following steps:

[0070] 1) Size: 2×5cm 2 The rectangular nickel foam was treated with ethanol, deionized water and 2M hydrochloric acid for 15 min in sequence, rinsed with deionized water and dried in a 60°C vacuum oven for later use;

[0071] 2) Weigh 0.08 g of dopamine hydrochloride into a 50 ml beaker, add 30 ml of deionized water, and stir on a magnetic stirrer to form a uniform transparent solution A;

[0072] 3) Weigh 0.2g Na2MoO4, 0.1g urea, 0.1g NH4F, 0.3g Ni(NO3)2·6H2O, 0.30g Co(NO3)2·6H2O, 0.40g Fe(NO3)3·9H2O, and 0.3g Cu(NO3)2·6H2O in a 50ml beaker, add 40mL of a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1, and sonicate until the raw materials are completely dissolved. This is labeled solution B.

[0073] 4) Under stirring conditions, slowly dripping solution B formed in step 3) into solution A, stirring for 15 minutes, to form solution C;

[0074] 5) placing the nickel foam treated in step 1) obliquely in a polytetrafluoroethylene reactor, adding solution C, hydrothermally reacting at 180° C. for 8 h, rinsing with deionized water, and drying in an oven at 60° C. to obtain a catalyst precursor;

[0075] 6) The precursor obtained in step 5) is heated to 500° C. at a rate of 5° C. / min in a 5% hydrogen / argon mixed atmosphere, kept warm for 2 hours, and then naturally cooled to obtain a nickel foam-supported nanorod composite catalyst composed of Fe, Co, Ni, Cu, and Mo elements, named FeCoNiCuMo / C@NF.

[0076] Example 4

[0077] A method for preparing a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material comprises the following steps:

[0078] 1) Size: 2×5cm 2 The rectangular nickel foam was treated with ethanol, deionized water and 2M hydrochloric acid for 15 min in sequence, rinsed with deionized water and dried in a 60°C vacuum oven for later use;

[0079] 2) Weigh 0.08 g of dopamine hydrochloride into a 50 ml beaker, add 30 ml of deionized water, and stir on a magnetic stirrer to form a uniform transparent solution A;

[0080] 3) Weigh 0.2g (NH4)2MoO4, 0.1g urea, 0.10g NH4F, 0.60g Ni(NO3)2·6H2O, 0.60g Co(NO3)2·6H2O, 0.40g Fe(NO3)3·9H2O, and 0.30g Cu(NO3)2·6H2O in a 50ml beaker, add 40mL of a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1, and sonicate until the raw materials are completely dissolved. Mark it as solution B;

[0081] 4) under stirring, slowly dripping solution B formed in step 3) into solution A, stirring for 15 minutes, to form solution C;

[0082] 5) placing the nickel foam treated in step 1) obliquely in a polytetrafluoroethylene reactor, adding solution C, hydrothermally reacting at 180° C. for 8 h, rinsing with deionized water, and drying in an oven at 60° C. to obtain a catalyst precursor;

[0083] 6) The precursor obtained in step 5) is heated to 500° C. at a rate of 5° C. / min in a 5% hydrogen / argon mixed atmosphere, kept warm for 2 hours, and then naturally cooled to obtain a nickel foam-supported nanorod composite catalyst composed of Fe, Co, Ni, Cu, and Mo elements, named FeCoNiCuMo / C@NF.

[0084] Example 5

[0085] Application of a carbon-assisted synthesis of FeCoNiCuMo / C@NF multi-metal composite material: Taking Example 1 as an example, the prepared composite catalyst FeCoNiCuMo / C@NF was electrochemically tested in 1M KOH solution to draw an LSV curve.

[0086] All tests in the present invention were carried out on a Shanghai Chenhua CHI 760E electrochemical workstation, and the electrochemical performance of the catalyst was evaluated using a three-electrode system, wherein the working electrode was the prepared self-supporting catalyst (1×2 cm), the reference electrode was a Hg / HgO electrode, the counter electrode was a carbon rod, and the electrolyte was 1M KOH. Using commercially used Pt / C and RuO2 as comparisons, the polarization curve of the catalyst was measured by linear sweep voltammetry (LSV), thereby studying the electrochemical hydrogen evolution (HER) and oxygen evolution (OER) performance of the catalyst.

[0087] Figure 4 Hydrogen evolution of the catalyst FeCoNiCuMo / C@NF and the noble metal catalyst obtained in Example 1 ( Figure 4 a) and oxygen evolution ( Figure 4 The LSV curve of (b) shows that the catalyst FeCoNiCuMo / C@NF exhibits excellent catalytic performance for hydrogen and oxygen evolution under alkaline conditions. For hydrogen evolution, only 18 mV is required to reach 10 mA cm -2 The current density of oxygen evolution reaction is only 149mV to reach 50mA·cm -2 The current density is 2.447 W / m; it can be seen that the catalyst can exhibit catalytic activity beyond that of precious metals. Figure 5 The performance curves of the catalyst FeCoNiCuMo / C@NF and the noble metal catalyst obtained in Example 1 are shown in Table 1. When the catalyst is used as both cathode and anode for the full water splitting test, Figure 5 As shown, only 1.59V is needed to reach 50mA·cm -2 Its performance exceeds the catalytic performance of commercially available precious metal electrodes and has great commercial value.

[0088] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-assisted FeCoNiCuMo / C@NF multi-metal composite material, characterized in that: The preparation method comprises the following steps: 1) Dispersing a nitrogen-containing polymer in water as solution A; mixing and dispersing a molybdenum source, urea, NH4F, a nickel source, a cobalt source, an iron source and a copper source in a solvent as solution B; dropping solution B into solution A, stirring, adding nickel foam to the obtained mixed solution, performing a hydrothermal reaction, and obtaining a precursor; 2) The precursor is pyrolyzed in a mixed atmosphere of hydrogen and argon to obtain a FeCoNiCuMo / C@NF multi-metal composite material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nitrogen-containing polymer, the molybdenum source, the urea and the NH4F in step 1) is: 0.04-0.16: 0.1-0.4: 0.1: 0.

1.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the atomic molar ratio of Mo in the molybdenum source, Ni in the nickel source, Co in the cobalt source, Fe in the iron source and Cu in the copper source is 1:1:0.5:0.1:0.1 to 1:2:2:1:

1.

4. The preparation method according to claim 1, characterized in that: The nitrogen-containing polymer in step 1) is any one of polydopamine PDA, chitosan CS or polyethyleneimine PEI.

5. The preparation method according to claim 1, characterized in that: In step 1), the solvent refers to a mixed solvent of anhydrous ethanol and water, and the volume ratio of anhydrous ethanol to water is 1:

1.

6. The preparation method according to claim 1 or 2, characterized in that: The molybdenum source in step 1) is Keggin type phosphomolybdic acid H3PMo 12 O 40 xH2O, sodium molybdate (Na2MoO4), ammonium molybdate ((NH4)2MoO4) any one.

7. The preparation method according to claim 1, characterized in that: The hydrothermal reaction conditions in step 1) are: hydrothermal reaction at 150-180° C. for 6-12 hours.

8. The preparation method according to claim 1, characterized in that: The pyrolysis in step 2) refers to heating to 400-600°C at a rate of 5°C / min and keeping the temperature for 2h.

9. A FeCoNiCuMo / C@NF multi-metal composite material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the FeCoNiCuMo / C@NF multi-metal composite material according to claim 9, characterized in that: Used in HER, OER and overall water splitting catalysis.